Application of oral inorganic iodine in the treatment of Graves’ disease - Huang, Yixuan; Xu, Yihang; Xu, Murong; Zhao, Xiaotong; Chen, Mingwei (Frontiers in Endocrinology, 2023)
Iodine is a crucial trace element for the human body and the basic raw material for the synthesis of thyroid hormones. Oral inorganic iodine includes dietary iodine and therapeutic iodine, both of which are closely associated with thyroid immunity and metabolism. Graves’ disease (GD), also known as diffuse toxic goiter, is characterized by hyperthyroidism and high iodine metabolism. Clinically, patients diagnosed with GD are often asked to limit iodine intake or even avoid iodine in their diet. The latest research has demonstrated that the interference of dietary iodine with antithyroid drugs (ATDs) treatment may be overestimated. In addition, as a medication for GD treatment, the administration of inorganic iodine has shown positive results in patients with mild hyperthyroidism, a low thyroid autoantibody concentration, a small thyroid volume, a high iodine diet and so on. Inorganic iodine may also be used as an alternative when patients experience side effects with traditional ATDs and for those who still prefer conservative treatment. Due to its low teratogenicity, blood toxicity and bone marrow toxicity, inorganic iodine plays a unique role in special populations, such as pregnant or lactating patients and patients receiving tumor radiotherapy or chemotherapy. In this review, the research progress, biological function, doses and effects, applicable populations and specific applications of dietary iodine and therapeutic iodine are summarized to provide references for the diagnosis and treatment of GD, thus improving the quality of life of GD patients.